Memantine protects the cultured rat hippocampal neurons treated by NMDA and amyloid β1–42 - Rozumna, Nataliia M.; Hanzha, Vita V.; Lukyanetz, Elena A. (Frontiers in Neuroscience, 2023)
Alzheimer's disease (AD) is a devastating neurodegenerative condition with no effective treatments. Recent research highlights the role of NMDA receptors in AD development, as excessive activation of these receptors triggers excitotoxicity. Memantine, an NMDA receptor antagonist, shows promise in curbing excitotoxicity. What sets our study apart is our novel exploration of memantine's potential to protect hippocampal neurons from neurotoxicity induced by NMDA and amyloid β1-42, a hallmark of AD. To achieve this, we conducted a series of experiments using rat hippocampal cell cultures. We employed Hoechst and propidium iodide double staining to assess neuronal viability. Analyzing the viability of neurons in normal conditions compared to their status after 24 hours of exposure to the respective agents revealed compelling results. The incubation of hippocampal neurons with NMDA or amyloid β1-42 led to a more than twofold increase in the number of apoptotic and necrotic neurons. However, when memantine was co-administered with NMDA or amyloid β1-42, we witnessed a notable augmentation in the number of viable cells. This unique approach not only suggests that memantine may act as a neuroprotective agent but also emphasizes the relevance of hippocampal neuron cultures as valuable models for investigating excitotoxicity and potential AD treatments.